Bullying-related adaptive psychological functioning scale for indonesian older primary school students: thematic analysis and initial items validation - Amalia Rahmandani; Erin Ratna Kustanti; Dinni Asih Febriyanti (Konselor, 2021)
Primary school supports early detection of psychological resources and potential disorders in students, because of the massive incidence and influence for the next life of bullying or peer victimization. It is also important for school to provide early intervention. The aim of the study was to develop a concept of psychological resources to adjust adaptively to bullying experiences, hereinafter referred to as bullying-related adaptive psychological functioning, in upper primary school students in Indonesia. This study carried out a thematic analysis of group interviews toward 60 students and resulted in the concept of bullying-related adaptive psychological functioning which is compiled from the themes of self-awareness, self-management, affiliate action, and positive expectations about oneself in the environment. Despite its limitations, there are 26 items resulting from the development of a psychological self-report using a Likert model. Self-awareness and self-management seem to be more difficult resources for students than the other two aspects.